Optimalisasi Pengelolaan Administrasi Sub Bagian Keuangan di Komisi Pemilihan Umum Kota Bandung - Wijaya, Fahmi; Apriyanti, Indri; Mahabatulloh, Khoirunnisa (Fisip UIN Sunan Gunung Djati Bandung, 2024)
Administration is a series of activities management processes to achieve the effectiveness and efficiency of organizational operations. In organizations such as the Bandung City General Election Commission (KPU), administration plays an important role in supporting the smooth running of democratic and transparent elections. One of the important parts of the Bandung City KPU is the Finance, General, and Logistics (KUL) Sub-Section, which is responsible for managing finances, general administration, and election logistics. This research was conducted qualitatively with a descriptive approach to support its observations. Data collection techniques were carried out through interviews, observations, and documentation during the Field Activity Practice activities of the Public Administration Department of UIN Sunan Gunung Djati Bandung. The results of this study indicate that administrative management in the KUL Sub-Section is carried out in a structured, transparent, and procedural manner. Because in order to ensure that every administrative step runs effectively and supports operational needs optimally. However, the management system is still carried out manually so that the adoption of information technology is needed in administrative management, such as the implementation of a digital administration system to increase efficiency and minimize the risk of damage to administrative management.